2017
DOI: 10.1101/111005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Architecture and Molecular Networks Underlying Leaf Thickness in Desert-Adapted TomatoSolanum pennellii

Abstract: Thicker leaves allow plants to grow in water-limited conditions. However, our understanding of the genetic underpinnings of this highly functional leaf shape trait is poor. We used a custom-built confocal profilometer to directly measure leaf thickness in a set of introgression lines (ILs) derived from the desert tomato species Solanum pennellii, and identified quantitative trait loci (QTL). We report evidence of a complex genetic architecture of this trait and roles for both genetic and environmental factors.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…Cell enlargement often occurs concomitantly with increases in ploidy levels during organogenesis in some plant species (Traas et al ., ; Kondorosi et al ., ; Sugimoto‐Shirasu and Roberts, ). Regarding leaf‐thickness growth, corresponding increases in cell size and ploidy levels were reported in Solanaceae species (Gauhl, ; Coneva et al ., ). In a recent study, the light‐shift experiment in Arabidopsis showed that exposure to HL conditions promoted the endocycle in Arabidopsis (Mohammed et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Cell enlargement often occurs concomitantly with increases in ploidy levels during organogenesis in some plant species (Traas et al ., ; Kondorosi et al ., ; Sugimoto‐Shirasu and Roberts, ). Regarding leaf‐thickness growth, corresponding increases in cell size and ploidy levels were reported in Solanaceae species (Gauhl, ; Coneva et al ., ). In a recent study, the light‐shift experiment in Arabidopsis showed that exposure to HL conditions promoted the endocycle in Arabidopsis (Mohammed et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Система была успешно использована для целого ряда фундаментальных и прикладных исследований. Например, детально изучена динамика фенотипических ответов С 4 -растений на дефицит азота и засуху [32]; найдена группа генов, контролирующих геометрию листа пасленовых [33]; описана эффективность функционирования фотосистемы II арабидопсиса и кукурузы [34] и др.…”
Section: лабораторные феномные платформыunclassified
“…Using two well known QTL/gene, fw2.2 and beta‐carotene ( B ), they demonstrated the high‐resolution mapping offered by the population. The genome of the S. pennellii accession was sequenced (Bolger et al ., ) and BILs enabled the characterization of QTL involved in yield (Soyk et al ., ), leaf shape (Fulop et al ., ), leaf thickness (Coneva et al ., ), and day length response (Müller et al ., ; Soyk et al ., ).…”
Section: Discovery Of Genetic Variations Underlying Major Traits In Tmentioning
confidence: 99%
“…For nearly two decades, ’omics technologies including transcriptomics, proteomics, and metabolomics have been used alone or in combination to discover genes and networks underlying various traits of interest in tomato. Examples of these are rootstock grafting (Ntatsi et al ., ), effect of root mycorhization on fruit quality (Zouari et al ., ), meristem maturation and inflorescence architecture (Park et al ., ; Soyk et al ., ), leaf morphology and thickness (Koenig et al ., ; Coneva et al ., ), glandular trichome metabolism (Balcke et al ., ), seed composition (Toubiana et al ., ), fruit set and parthenocarpy (Wang et al ., ; Ruiu et al ., ), and fruit development, ripening, and composition (Carrari et al ., ; Faurobert et al ., ; Mintz‐Oron et al ., ; Mounet et al ., ; Matas et al ., ; Osorio et al ., ; Itkin et al ., ; Pan et al ., ; Pattison et al ., ; Fernandez‐Moreno et al ., ; Szymanski et al ., ; Li et al ., ; Shinozaki et al ., ; Stevens et al ., ). While fruit studies outnumber all others, considerable efforts have also been devoted to the study of abiotic stress, including heat (Keller and Simm, ), cold (Cruz‐Mendívil et al ., ; Barrero‐Gil et al ., ; Ntatsi et al ., ), water limitation (Albert et al ., ), salinity stress (Zhang et al ., ) and nutrient deficiency (Zamboni et al ., ), and of plant reaction to biotic stress, causes of which include viruses (Ramesh et al ., ), bacteria (French et al ., ), fungi (Blanco‐Ulate et al ., ; Ghosh et al ., ), and nematodes (Święcicka et al ., ).…”
Section: Accelerating Trait Discovery In Tomato Using Deep Sequencingmentioning
confidence: 99%